Internationalization Misconceptions - De Wit, Hans (International Higher Education, 2011)
Mainstreaming of internationalization assumes a more integral process-based approach of internationalisation. Still there is a predominantly activity- oriented or even instrumental approach towards internationalization. Nine misconceptions are described, whereby internationalization is regarded as synonymous with a specific programmatic or organizational strategy to promote internationalization.